Molecular Targets for Biological Therapies of Severe Asthma - Pelaia, Corrado; Crimi, Claudia; Vatrella, Alessandro; Tinello, Caterina; Terracciano, Rosa; Pelaia, Girolamo (Frontiers in Immunology, 2020)
Asthma is a heterogeneous respiratory disease characterized by usually reversible bronchial obstruction, which is clinically expressed by different phenotypes driven by complex pathobiological mechanisms (endotypes). Within this context, during the last years several molecular effectors and signalling pathways have emerged as suitable targets for biological therapies of severe asthma, refractory to standard treatments. Indeed, various therapeutic antibodies currently allow to intercept at different levels the chain of pathogenic events leading to type 2 (T2) airway inflammation. In addition to pro-allergic immunoglobulin E (IgE), that chronologically represents the first molecule against which an anti-asthma monoclonal antibody (omalizumab) was developed, today other targets are successfully exploited by biological treatments of severe asthma. In particular, pro-eosinophilic interleukin 5 (IL-5) can be targeted by mepolizumab or reslizumab, whereas benralizumab is a selective blocker of IL-5 receptor. Moreover, dupilumab behaves as a dual receptor antagonist of pleiotropic interleukins 4 (IL-4) and 13 (IL-13). Besides these drugs that are already available in medical practice, other biologics are under clinical development such as those targeting innate cytokines, also including the alarmin thymic stromal lymphopoietin (TSLP), which plays a key role in the pathogenesis of type 2 asthma. Therefore, ongoing and future biological therapies are significantly changing the global scenario of severe asthma management. These new therapeutic options make it possible to implement phenotype/endotype-specific treatments, that are delineating personalized approaches precisely addressing the individual traits of asthma pathobiology. Such tailored strategies are thus allowing to successfully target the immune-inflammatory responses underlying uncontrolled T2-high asthma.